2016
DOI: 10.1111/cei.12787
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cellular immunological responses in mono- and polymorphic clinical forms of post-kala-azar dermal leishmaniasis in India

Abstract: SummaryPost-kala-azar dermal leishmaniasis (PKDL) is a chronic dermal complication that occurs usually after recovery from visceral leishmaniasis (VL). The disease manifests into macular, papular and/or nodular clinical types with mono-or polymorphic presentations. Here, we investigated differences in immunological response between these two distinct clinical forms in Indian PKDL patients. Peripheral blood mononuclear cells of PKDL and naive individuals were exposed in vitro to total soluble Leishmania antigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…We analyzed the capacity of Ld Cen1 −/− and Ld p27 −/− to stimulate TNF-α and found that similar to IL-12, significantly higher stimulation of TNF-α was seen only in the HVL and PKDL groups. The observed increase in production of Th1 cytokines (IFN-γ, TNF-α and IL-12) in Leishmania exposed group (HVL or PKDL) compared to naive or active VL individual in response to live attenuated or wild type Leishmania parasites, is in accordance with earlier studies carried out with Leishmania antigen in HVL and PKDL groups 33 34 40 44 . Further, this increase in Th1 cytokine production in pre-exposed group suggested that the live attenuated parasites can induce protective effector response from memory response generated during resolution of infection in HVL individuals.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We analyzed the capacity of Ld Cen1 −/− and Ld p27 −/− to stimulate TNF-α and found that similar to IL-12, significantly higher stimulation of TNF-α was seen only in the HVL and PKDL groups. The observed increase in production of Th1 cytokines (IFN-γ, TNF-α and IL-12) in Leishmania exposed group (HVL or PKDL) compared to naive or active VL individual in response to live attenuated or wild type Leishmania parasites, is in accordance with earlier studies carried out with Leishmania antigen in HVL and PKDL groups 33 34 40 44 . Further, this increase in Th1 cytokine production in pre-exposed group suggested that the live attenuated parasites can induce protective effector response from memory response generated during resolution of infection in HVL individuals.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, we observed significantly higher stimulation of IFN-γ in HVL and PKDL group as compared to the control uninfected cells and healthy group. Leishmanial antigens have previously been shown to induce stimulation of IFN-γ in PKDL and healed cases of VL, asymptomatic VL, cutaneous and mucocutaneous leishmaniasis 33 34 35 36 37 . In the present study significantly higher stimulation of IFN-γ was also found in the VL group as compared to the healthy group.…”
Section: Discussionmentioning
confidence: 99%
“…The IFN‐γ‐driven Type 1 immune response to CL is both associated with a good prognosis, and also contributes significantly to immunopathology 1 . This protective‐but‐damaging immune response in CL is known to be dominated by CD4 + T cells and cytotoxic CD8 + T cells, which display cytotoxic functions 2,3 . It has also become apparent that other populations of cytotoxic cells, including Natural Killer (NK) cells may also contribute to pathogen clearance in CL 4 .…”
mentioning
confidence: 99%
“…1 This protective-but-damaging immune response in CL is known to be dominated by CD4 + T cells and cytotoxic CD8 + T cells, which display cytotoxic functions. 2,3 It has also become apparent that other populations of cytotoxic cells, including Natural Killer (NK) cells may also contribute to pathogen clearance in CL. 4 In order to develop improved strategies for vaccination or develop strategies for therapeutic control post-infection, it is important to understand the contributions of immune cells to both pathogen clearance and to the infection-induced pathology.…”
mentioning
confidence: 99%
“…Post-kala-azar dermal leishmaniasis is a chronic dermal complication that occurs usually after recovery from visceral leishmaniasis. There was a raised proportion of circulating NKT cells in these patients compared to health controls [ 34 ]. Karmakar and colleagues isolated a natural ligand of NKT cells, β -(1–4)-galactose terminal glycosphingophospholipid (GSPL) from this parasite to treat infected BALB/c mice.…”
Section: Nkt Cells In Parasitic Infectionsmentioning
confidence: 99%